Assessing Nutritional Status, Quality of Work-Life, And Turnover Intentions of Millennials in Malaysian Banks - Abdullah, Nor Azimah Chew; Zakaria, Nazlina (Universiti Utara Malaysia, 2022)
This research focused on identifying the relationship of nutritional status and quality of work-life with turnover intentions of millennials in Malaysian banks. Nutritional status was further sub constructed into healthy eating habits and nutritional self-efficacy. This research was conducted in capital cities of Northern states of Malaysia. Data was collected through an online survey, and 113 usable responses were received from 50 banks. Results revealed that healthy eating habits and nutritional self-efficacy of millennial bank employees increase their quality of work-life. Whereas, healthy eating habits does not affect turnover intentions of the employees, and nutritional self-efficacy increase their turnover intentions. Results further revealed that the quality of work-life not only reduce the turnover intentions of the employees, but it also negatively mediates the relationship between nutritional status and turnover intentions. Hence, banks should focus on enhancing their quality of work-life and provide healthy environment to their employees to reduce their turnover rate.